STUDI KOMPARASI PRAKTIK KEPEMIMPANAN VISIONER KEPALA MADRASAH IBTIDAIYAH (Studi Pada MI Istiqomah Sambas Purbalingga dan MI Ma’arif NU 1 Pageraji Banyumas) - Nur Mukti (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
Research conducted by the author of Visionary Leadership PracticesComparative Study of the Head of Government Elementary School (Studies in Sambas Purbalingga Istiqomah MI and MI Maarif NU 1 Pageraji Banyumas), it could be concluded that the equation of visionary leadership practice headmaster seen from the process of transforming and implementing the vision of madrasas, Transforming the vision in madrasas, the vision is equally socialized to the teacher, then the parent forum. Later in Implementing the vision madrasah, gather accordingto the work programmeof madrasah. The differents of layout that is in the process of creating and formulate vision madrasah